2004
DOI: 10.1097/01.npt.0000284773.87060.c8
|View full text |Cite
|
Sign up to set email alerts
|

Interrater and Intrarater Reliability of the Tinetti Balance Test for Individuals with Amyotrophic Lateral Sclerosis

Abstract: Background and Purpose: Individuals with amyotrophic lateral sclerosis (ALS) develop balance problems. This study was conducted to determine the reliability of the Tinetti Balance Test for individuals with ALS. Subjects and Methods: Subjects in Stages I -III volunteered for Parts 1 (n=21) and 2 (n=11). One physical therapist and 2 physical therapy students (Part 1) rated subjects' live performances of the Tinetti Balance Test. Two physical therapists and 4 physical therapy students (Part 2) rated videotaped pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
3
18
0
1
Order By: Relevance
“…Another study reported higher ICC values (>0.80) for both intra-and interrater reliability of the POMA scale in Parkinson's disease [38]. In patients with amyotrophic lateral sclerosis, intra-and interrater reliability of the balance subscale were found to be excellent as assessed by ICCs (>0.90) [39].…”
Section: Discussıonmentioning
confidence: 95%
“…Another study reported higher ICC values (>0.80) for both intra-and interrater reliability of the POMA scale in Parkinson's disease [38]. In patients with amyotrophic lateral sclerosis, intra-and interrater reliability of the balance subscale were found to be excellent as assessed by ICCs (>0.90) [39].…”
Section: Discussıonmentioning
confidence: 95%
“…9 -20 The balance and gait subscales that form the TMT have been studied individually or combined as in this study. 8, 10,11,19 The TMT predicts falls among elderly individuals 9,11,13,14 ; those scoring 19 to 24 out of 28 on the TMT have a "moderate" risk for falling, and individuals scoring Ͻ19 have a "high" risk for falling. 21 The TMT was found to have the best predictive validity for fall risk in elderly people when compared with the TUG, FRT, and one-leg stance test.…”
mentioning
confidence: 99%
“…Consequently, the total Tinetti Test score ranges between 0 to 28 points. The higher score indicating a better performance [24]. All these outcomes measure were used to evaluate the trunk performance, trunk lateral flexion ROM, balance and gait respectively before the intervention and after 4 weeks of intervention.…”
Section: Outcomes Measurementioning
confidence: 99%